2015
DOI: 10.1007/s00500-015-1642-4
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive memetic algorithm for minimizing distance in the vehicle routing problem with time windows

Abstract: This paper presents an adaptive memetic algorithm to solve the vehicle routing problem with time windows (VRPTW). It is a well-known NP-hard discrete optimization problem with two objectives-to minimize the number of vehicles serving a set of geographically dispersed customers, and to minimize the total distance traveled in the routing plan. Although memetic algorithms have been proven to be extremely efficient in solving the VRPTW, their main drawback is an unclear tuning of their numerous parameters. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…The results do not show a clear prevalence of any of them, but confirming the significance of those additional costs and externalities. In [13] the adaptive memetic algorithm for minimizing distance in vehicle routing problem with time windows (VRPTW) is described. In [14], different metaheuristic approaches for solving VRPTW are described, such as Particle Swarm Optimization (PSO), Ant Colony Optimization (ACO) or Artificial Bee Colony (ABC).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The results do not show a clear prevalence of any of them, but confirming the significance of those additional costs and externalities. In [13] the adaptive memetic algorithm for minimizing distance in vehicle routing problem with time windows (VRPTW) is described. In [14], different metaheuristic approaches for solving VRPTW are described, such as Particle Swarm Optimization (PSO), Ant Colony Optimization (ACO) or Artificial Bee Colony (ABC).…”
Section: Related Workmentioning
confidence: 99%
“… The unloading time for the customer which will be used in the following steps of the proposed algorithm is equal to: (12)  The time window of the customer for use in later steps of the algorithm is equal to: (13)  When all customers are checked, the iterations are stopped Besides the listed transformations, other data preparations are done before the start of the algorithm's execution. The listed preparations of the algorithm's input data will be explained later in the following sections of this work.…”
Section: Pre-step -Data Initialization and Transformationsmentioning
confidence: 99%
“…Finally, a multiperior VRP with profit is addressed by a memetic algorithm in [27]. Works cited in this paragraph are some recent and interesting examples of the whole literature, some other recent examples can be found in, for example, [28,29,30]. Therefore, in this paper one metaheuristic proposed a few years ago is used to solve the presented problem.…”
Section: Introductionmentioning
confidence: 99%
“…Besides,[59][60][61] investigated the Cumulative CVRP in which the objective is to minimize the sum of arrival times at customers rather than total routing cost or distance.The authors concluded that this problem constitutes a good way to model situations where arrival time at customers is very important such as after natural disasters.Moreover, Lei et al[62] and Eufinger et al[63] incorporated some uncertainty in their studies; the former authors developed a neighborhood search heuristic to solve the problem with stochastic demands while the latter authors came up with a robust approach that takes travel times uncertainty into account. Results confirmed the superiority of the proposed heuristics over an alternative solution approaches.…”
mentioning
confidence: 99%